Influence of initial damage distribution and sinks in fusion materials: A parametric OKMC study of W vs Fe - Jintong Wu; Juan-Pablo Balbuena; Ville Jantunen; Maria J. Caturla; Fredric Granberg (Nuclear Materials and Energy)
Irradiation present in nuclear test reactors and power plants is known to alter the properties of structural materials. Using long-timescale Object Kinetic Monte Carlo simulations, we systematically investigated the influence of different parameters and temperature on the microstructural evolution of tungsten and iron under irradiation. Our results indicate that in tungsten, the inclusion of spherical absorbers is essential for achieving realistic vacancy saturation levels by limiting the recombination between highly mobile interstitials and vacancies. At elevated temperatures, using cascade-shaped insertion enhances local vacancy clustering, leading to a larger number of smaller vacancy clusters compared to random insertion. In contrast, for iron, the absence of spherical absorbers facilitates the growth of immobile C15 clusters and subsequent formation of 〈100〉 loops, markedly altering the defect distribution even at room temperature. Additionally, while the dose rate effect is negligible at room temperature in tungsten due to the immobile vacancies and the very fast migration of interstitials, longer relaxation times between cascades at higher temperatures promote the development of larger vacancy clusters. These insights are crucial for realistic parameterization of Kinetic Monte Carlo models and contribute to a deeper understanding of the irradiation effects in materials used in nuclear applications.